Soluplus-Mediated Diosgenin Amorphous Solid Dispersion with High Solubility and High Stability: Development, Characterization and Oral Bioavailability - Liu P; Zhou J; Chang J; Liu X; Xue H; Wang R; Li Z; Li C; Wang J; Liu C (Dove Medical Press, 2020)
Pei Liu,1,2 Jian-yu Zhou,2 Jin-hua Chang,2 Xi-gang Liu,2 He-fei Xue,2 Ru-xing Wang,2 Zhong-si Li,2 Chun-shi Li,3 Jian Wang,3 Cui-zhe Liu1,2 1Department of Pharmaceutics, School of Pharmacy, Shenyang Pharmaceutical University, Shenyang 110016, People’s Republic of China; 2Hebei Province Key Laboratory of Research and Development for Chinese Medicine, Chengde Medical University, Chengde, Hebei 067000, People’s Republic of China; 3Key Laboratory of Structure-Based Drug Design & Discovery of Ministry of Education, Shenyang Pharmaceutical University, Shenyang 110016, People’s Republic of ChinaCorrespondence: Cui-zhe Liu 103 Wenhua Road, Shenyang 110016, People’s Republic of ChinaTel +86-0314-2291142Email liucuizhexy@163.comJian WangHebei Province Key Laboratory of Research and Development for Chinese Medicine, Chengde Medical University, Chengde, Hebei 067000, People’s Republic of ChinaTel +86-13604051904Email jianwang@email.comBackground and Purpose: The traditional Chinese medicine, diosgenin (Dio), has attracted increasing attention because it possesses various therapeutic effects, including anti-tumor, anti-infective and anti-allergic properties. However, the commercial application of Dio is limited by its extremely low aqueous solubility and inferior bioavailability in vivo. Soluplus, a novel excipient, has great solubilization and capacity of crystallization inhibition. The purpose of this study was to prepare Soluplus-mediated Dio amorphous solid dispersions (ASDs) to improve its solubility, bioavailability and stability.Methods: The crystallization inhibition studies were firstly carried out to select excipients using a solvent shift method. According to solubility and dissolution results, the preparation methods and the ratios of drug to excipient were further optimized. The interaction between Dio and Soluplus was characterized by differential scanning calorimetry (DSC), fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), powder X-ray diffraction (PXRD) and molecular docking. The pharmacokinetic study was conducted to explore the potential of Dio ASDs for oral administration. Furthermore, the long-term stability of Dio ASDs was also investigated.Results: Soluplus was preliminarily selected from various excipients because of its potential to improve solubility and stability. The optimized ASDs significantly improved the aqueous solubility of Dio due to its amorphization and the molecular interactions between Dio and Soluplus, as evidenced by dissolution test in vitro, DSC, FT-IR spectroscopy, SEM, PXRD and molecular docking technique. Furthermore, pharmacokinetic studies in rats revealed that the bioavailability of Dio from ASDs was improved about 5 times. In addition, Dio ASDs were stable when stored at 40°C and 75% humidity for 6 months.Conclusion: These results indicated that Dio ASDs, with its high solubility, high bioavailability and high stability, would open a promising way in pharmaceutical applications.Keywords: diosgenin, amorphous solid dispersions, solubility, bioavailability, stability